Kapasitas Adsorpsi Biomassa Paku Air (Lemna minor linn) Teresterifikasi Oleh Asam Sitrat Terhadap Mangan(Ii) - Anita Anita; Titin Anita Zaharah; Ajuk Sapar (Study Program of Chemistry - Alauddin State Islamic University of Makassar, 2020)
Research on the adsorption of Mn (II) ions has been carried out using biomass duckweed (Lemna minor linn) with the esterified by citric acid. This study aims to determine the maximum adsorption capacity of Mn (II) ions in using adsorbent biomass of duckweed esterified by citric acid. Water nail biomass adsorbents were characterized using FTIR to determine the functional groups of citric acid esterified adsorbents. The stages of this research include modification of water biomass using citric acid, followed by manganese (II) ion adsorption tests with pH variations in pH, contact time of adsorption and initial concentration variations under optimum conditions. The results showed that optimum adsorption occurred at pH 5, contact time for 10 minutes and the concentration of Mn (II) solution 15 mg / L was measured using atomic absorption spectrophotometry. The equation used in the study follows the Langmuir and Freundlich equations. Based on the Langmuir isotherm equation, the maximum adsorption capacity of Mn (II) ion using citric acid modified water nail biomass is 7,645 mg/ g, the equilibrium constant is 4,317 L/ mol and the adsorption energy is 36,84039 KJ / mol.